Marketing channels for irrigated exotic vegetables - Henseler, M.; Amoah, Philip (2014)
This chapter provides qualitative and quantitative information on the distribution pathways of irrigated vegetables, with a focus on lettuce, produced in Kumasi and Accra from the farm to the consumer. The data from a survey carried out in 2005 show the contribution of irrigated urban farming and the size of the beneficiary group in Accra, which is also the group at risk from crop contamination which has been quantified.